Narcolepsy: a case report and review of literature - Baltakytė , E.; Popa , A.; Pajėdienė , E. (Neurologijos seminarai, 2019)
Narcolepsy is one of the central hypersomnias associated with a tetrad of symptoms: excessive daytime sleepiness, cataplexy, sleep paralysis, and hypnagogic hallucinations. On average, the accurate diagnosis of narcolepsy is made after 10.5 years after the onset of the disease, therefore the treatment is delayed causing a reduced quality of life. In this paper we present a clinical case of narcolepsy type 1 causing both diagnostic and therapeutic challenges. Furthermore, the most common symptoms of narcolepsy, diagnosis, treatment options as well as possibilities to implement them in Lithuania are overviewed in this article.